PENERAPAN KEBIJAKAN RESTRUKTURISASI PEMBIAYAAN KONSUMER BERMASALAH PADA BANK SYARIAH DIMASA PANDEMI - Mira Maulida (2022)
The Covid-19 pandemic has had an impact on almost all fields in the world. One sector that gets a significant influence is the economic sector which causes a decrease in the number of people's income. Therefore, the government, in particular the Financial Services Authority (OJK), enforces regulations that have been issued in accordance with PJOK Number 11/PJOK.03/2020 concerning National Economic Stimulus as a Countercyclical Impact of the 2019 Coronavirus Discae Spread. for the Bank. The implementation of financing restructuring for customers who have potential problems but still have good business prospects will have a positive impact on fulfilling customer obligations. The restructuring aims to help financing problem customers to be able to fulfill loan refinancing, so that the bank does not suffer losses. This final project was prepared with the aim of knowing and conducting a review of the implementation of a non-performing financing restructuring policy in Islamic Banks during this pandemic. Based on the results of data processing, the number of debtors whose financing is being restructured continues to grow each period. The results of this paper indicate that Islamic banks have effectively implemented financing restructuring in reducing NPF or Non-Performing Finance.